Synthesis and structure of an organobismuth (V) dithiocarbamate polymer [PhBiS2CN(CH3)2Cl]n and its use as a high-efficiency photocatalysis for organic dyes degradation. Issue 11 (2nd November 2017) - Cui, Lian-Sheng; Meng, Jun-Rong; Gan, Yong-Le; Li, Yuan-Cheng
ABSTRACT: A new Bi(V) coordination polymer, namely, [PhBiS2 CN(CH3 )2 Cl]n has been synthesized and characterized by element alanalysis, IR, 1 H NMR and X-ray single-crystal diffraction. X-ray single-crystal diffraction study reveals that the complex features one-dimensional spiral chain structure by a bridging chlorine atom to link metal ions and two adjacent chains bridged by C-H—C interactions appear double helix structure. The complex displays highly photocatalytic degradation activity for methylene blue, rhodamine B and methyl violet.